The Relationship of Entrepreneurial Capabilities, Performance and Personality Traits on the Job Satisfaction of Tourism Industry (Case of Nepal) - Thapa, Renu (Graduate School of International Studies Ajou University, 2015)
The impact and relationship of capabilities, personality traits and performance has resurfaced in entrepreneurship research on job satisfaction. The research surrounding the broad personality traits performance and capabilities has varied. Although capabilities, extraversion and neuroticism have been found to generally have a positive relationship with entrepreneurial job satisfaction level. Conflicting and inconsistent results have emerged therefore an in depth look at the facets of extraversion, neuroticism, and capabilities may offer additional information. The present investigation used as sample of owner, manager and both owner and manager. Especially it was hypothesized that conscientiousness was negative relation to the entrepreneur’s satisfaction. Extraversion and neuroticism were positively impact to entrepreneurial satisfaction. The hypotheses were tested using hierarchical multiple regression, full support was found for capabilities and extraversion. These four hypothesis explanation could be that entrepreneurship is a process that foes through phases where each has a different set of activities and outcomes, and the effects of these four hypothesis may change over the different phases of founding a new venture and job satisfaction level of the entrepreneurs in tourism industry. Several result supported previous research findings. Contribution and future research ideas are discussed.
학위논문(석사)--아주대학교 Graduate School of International Studies :국제경영학과,2015. 2